2020
DOI: 10.1021/acssynbio.9b00410
|View full text |Cite
|
Sign up to set email alerts
|

A Small-Molecule-Responsive Riboswitch Enables Conditional Induction of Viral Vector-Mediated Gene Expression in Mice

Abstract: Adeno-associated viral (AAV) vector-mediated gene therapy holds great potential for future medical applications. However, to facilitate safer and broader applicability and to enable patient-centric care, therapeutic protein expression should be controllable, ideally by an orally administered drug. The use of protein-based systems is considered rather undesirable, due to potential immunogenicity and the limited coding space of AAV. Ligand-dependent riboswitches, in contrast, are small and characterized by an at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 50 publications
2
45
1
Order By: Relevance
“…We used AAV2, AAV8, AAV9, AAV2.7m8 (Dalkara et al, 2013), ShH10 (Klimczak et al, 2009), and AAV2.NN, AAV2.GL (Pavlou et al, 2021) with the ss expression cassettes ss-CMV-eGFP-SV40poly(A), ss-CMV-anti-FITC, or sc-CMV-eGFP-SV40poly(A) (Strobel et al, 2020), flanked by AAV2-derived inverted terminal repeats. AAV vectors were prepared as in Strobel et al (2019): HEK 293-H cells were cultured in DMEM + GlutaMAX-I + 10% FCS (Thermo Fisher Scientific) and transfected as previously described (Strobel et al, 2015).…”
Section: Aav Vectorsmentioning
confidence: 99%
“…We used AAV2, AAV8, AAV9, AAV2.7m8 (Dalkara et al, 2013), ShH10 (Klimczak et al, 2009), and AAV2.NN, AAV2.GL (Pavlou et al, 2021) with the ss expression cassettes ss-CMV-eGFP-SV40poly(A), ss-CMV-anti-FITC, or sc-CMV-eGFP-SV40poly(A) (Strobel et al, 2020), flanked by AAV2-derived inverted terminal repeats. AAV vectors were prepared as in Strobel et al (2019): HEK 293-H cells were cultured in DMEM + GlutaMAX-I + 10% FCS (Thermo Fisher Scientific) and transfected as previously described (Strobel et al, 2015).…”
Section: Aav Vectorsmentioning
confidence: 99%
“…One tetracycline aptazyme, Tc40, enabled over 20-fold suppression in human cells and also achieved 7-fold suppression of an AAVdelivered transgene through oral administration of tetracycline in a mouse model. Strobel et al also recently demonstrated 15-fold induction of an AAV-delivered transgene in mice using a tetracycline-regulated aptazyme on-switch developed through a similar rational design and testing approach [154]. This result also represents a rare case in which switch performance was higher in an animal model than in previous results in cell culture [136].…”
Section: Improving the Function Of Aptazyme Riboswitchesmentioning
confidence: 91%
“…AAV2, AAV8, AAV9, AAV2.7m8 (Dalkara et al, 2013), ShH10 (Klimczak et al, 2009), and AAV2.NN, AAV2.GL (Pavlou et al, 2021) with the single stranded (ss) expression cassettes; ss-CMV-eGFP-SV40polyA, ss-CMV-antiFITC or self complementary (sc) sc-CMV-eGFP-SV40polyA, (Strobel et al, 2020) flanked by AAV2-derived inverted terminal repeats were applied. AAV vectors were prepared as previously described (Strobel et al, 2019).…”
Section: Methodsmentioning
confidence: 99%